2014
DOI: 10.1111/1468-0106.12066
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Price Dispersion and Dynamics in Laboratory Bertrand Markets

Abstract: This paper develops a quantal-response adaptive learning model which combines sellers' bounded rationality with adaptive belief learning in order to explain price dispersion and dynamics in laboratory Bertrand markets with perfect information. In the model, sellers hold beliefs about their opponents' strategies and play quantal best responses to these beliefs. After each period, sellers update their beliefs based on the information learned from previous play. Maximum likelihood estimation suggests that when se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…PQRE requires the expected payoffs for all prices to be positive. In empirical applications, this restriction on expected payoffs is usually imposed by experimental design or by adding a small positive constant to the payoffs for all prices (e.g., Bayer, Wu, & Chan, ).…”
Section: Qre In a Homogeneous Bertrand Oligopolymentioning
confidence: 99%
See 1 more Smart Citation
“…PQRE requires the expected payoffs for all prices to be positive. In empirical applications, this restriction on expected payoffs is usually imposed by experimental design or by adding a small positive constant to the payoffs for all prices (e.g., Bayer, Wu, & Chan, ).…”
Section: Qre In a Homogeneous Bertrand Oligopolymentioning
confidence: 99%
“…PQRE requires the expected payoffs for all prices to be positive. In empirical applications, this restriction on expected payoffs is usually imposed by experimental design or by adding a small positive constant to the payoffs for all prices (e.g., Bayer, Wu, & Chan, 2014). Baye and Morgan (2004) show that for λ N < 1 ( − 1) ∕ there exists a closed-form representation for a symmetric PQRE choice function.…”
Section: Lqre and Pqre In A Bertrand Oligopolymentioning
confidence: 99%
“…First, it is indicated that consumers need information on the offerings available in the market (Barron et al, 2004;Liu et al, 2012). To gather this information, customers must engage in search activities, which produce costs (Baye et al, 2004b;Bayer et al, 2013;Chandra and Tappata, 2011). Some customers are not willing or able to bear the incorporated search costs (Chandra and Tappata, 2011;Sorensen, 2000), ultimately leading to a market which includes well informed and less informed customers (Chen and Zhang, 2011;Morgan et al, 2006).…”
Section: Homogenous Product Price Dispersion In Competitive Environme...mentioning
confidence: 99%
“…Experimental and empirical studies robustly find deviations from equilibrium, with prices showing significant dispersion. In the second paper of this issue, 'Explaining price dispersion and dynamics in laboratory Bertrand markets', Bayer et al (2014) introduce a new class of learning models with the following features. Players form beliefs about an opponent's action choice using a weighted fictitious play process.…”
mentioning
confidence: 99%
“…An interesting aspect of this model is that it is a generalization of the quantal response equilibrium (McKelvey and Palfrey, 1995). Bayer et al (2014) show that their generalization captures the pricing dynamics well and, therefore, is an appropriate model when there is complete information.…”
mentioning
confidence: 99%